Promosi, Electronic Word of Mouth dan Persepsi Keamanan terhadap Minat Beli melalui Kepercayaan Konsumen sebagai Variabel Intervening - Debby Handayani (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This research aims to analyze the effect of promotion, electronic word of mouth, and perceived security to purchase intention with consumer trust as an intervening variable. This research is quantitative. The data collection method used a questionnaire with a sample of 100 shopee consumers in Padang. The analytical method used is Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS) with SmartPLS software version 3.3.3. The results showed that Promotion has a positive and significant effect on consumer trust. Electronic word of mouth has a positive and significant effect on consumer trust. Perceived security has a positive and significant effect on consumer trust. Promotion has a positive and significant effect on purchase intention. Electronic word of mouth has a positive and significant effect on purchase intention. Perceived security has a positive and significant effect on purchase intention. Consumer trust has a positive and significant effect onpurchase intention. Promotion through consumer trust has a positive but not significant effect on purchase intention. Electronic word of mouth through consumer trust has a positive but not significant effect on purchase intention. Perceived security through consumer trust has a positive but not significant effect on purchase intention. It means consumer trust is not mediate the influence of promotion, electronic word of mouth, and perceived security on purchase intention